Modernization of Education in Pakistan: A Case Study - Fareeda Ibad (International Journal of Experiential Learning & Case Studies)
The developing world is grappling with diverse educational trends in their quest to become globalized and to keep pace with the developed world. This quest is by no means the prime motivator. What is of importance is the development of the nation in terms of the moral, political, socio-economic, and cultural perspective. Education theories which emerged in the efforts for the ‘modernization’ of education, namely the Common World Educational Culture Theory and the Globally Structured Agenda for Education Theory have been the subject of evolution over time with the present trends favoring post modern education or as it may be simplified, ‘experiential learning’, that is, learning by doing. The developing world is grappling with these educational trends. This paper attempts to examine the ‘modernization’ of education in Pakistan with reference to an institution selected for the purpose of the study. In this context a premier business institution has been considered as a point of reference and its curriculum and education philosophy have been examined through document analysis to determine what education theory it subscribes to and what its aims are in the future. The document analysis of the catalog and curriculum led to the conclusion that the education philosophy of the institution is modern; however, extracurricular activities are inclined to be postmodern.